Development of excel VBA program for small drainage network evaluation based on rational method of MSMA 2 / Mohamad Irwan P. Harahap and Muhammad Hafiz Azmi - P. Harahap, Mohamad Irwan; Azmi, Muhammad Hafiz (2017)
Torrential rainfall and resulting flood causing widespread life disruptions and material losses are real and recurring problems in Malaysia. These catastrophes have usually been attributed among others to the inadequacy of the existing drainage network and lackadaisical maintenance efforts. It would be interesting to point out that much of the inherited and currently operational drainage system was designed and developed using the conventional concept of rapid disposal, localized reactive and mono-functional drainage with the consequent of unchecked non-permeable surface growth, unimpeded runoff generation, and perpetual and eventually unrealized drainage upgrade further downstream. The advent of MSMA now in its 2nd edition is meant to provide a paradigm shift in storm water management thinking specifically with the containment of runoff at the source and doing away with the unsustainable policy of perpetual system upgrade following adjoining land development. As in many an application in the industry as well as academia, migration to a new thinking or work process would be greatly facilitated and expedited with the aid of ICT tools. Excel VBA provides such a familiar, common, and convenient platform to develop intensive and quite engaging computational processes occasionally with the look and feel of commercial software but at fraction of the cost and practically reutilizing existing resources. Such development was addressed in this paper and used to solve a real world project, the results of which were in agreement with manual computations.